Consecutive four-component synthesis of trisubstituted 3-iodoindoles by an alkynylation–cyclization–iodination–alkylation sequence - Ledermann, Nadia; Moubsit, Alae-Eddine; Müller, Thomas J. J. (Beilstein Journal of Organic Chemistry, 2023)
A library of 19 differently substituted 3-iodoindoles is generated by a consecutive four-component reaction starting from ortho-haloanilines, terminal alkynes, N-iodosuccinimide, and alkyl halides in yields of 11–69%. Initiated by a copper-free alkynylation, followed by a base-catalyzed cyclizive indole formation, electrophilic iodination, and finally electrophilic trapping of the intermediary indole anion with alkyl halides provides a concise one-pot synthesis of 3-iodoindoles. The latter are valuable substrates for Suzuki arylations, which are exemplified with the syntheses of four derivatives, some of them are blue emitters in solution and in the solid state, in good yield.
Keywords: alkynylation; catalysis; cyclization; indoles; iodination; multicomponent reactions